The role of face masks within in-patient psychotherapy: Results of a survey among inpatients and healthcare professionals - Erschens, Rebecca; Adam, Sophia Helen; Weisshap, Chiara; Giel, Katrin Elisabeth; Wallis, Hannah; Herrmann-Werner, Anne; Festl-Wietek, Teresa; Mazurak, Nazar; Zipfel, Stephan; Junne, Florian (Frontiers in Neuroscience, 2022)
Introduction Face-to-face medical and psychotherapeutic treatments during the Corona pandemic often involve patients and health care providers wearing face masks. We performed a pilot survey assessing the subjective experience of wearing face masks during psychotherapy sessions regarding (i) feasibility, (ii) psychotherapeutic treatment and (iii) communication, emotion and working alliance in patients and healthcare professionals. Methods A total of n = 62 inpatients (RR = 95.4%) and n = 33 healthcare professionals (RR = 86.8%) at an academic department of Psychosomatic Medicine and Psychotherapy participated in this survey anonymously. The items of the questionnaire were created by the interprofessional expert team and were based on existing instruments: (i) the Therapeutic Relationship Questionnaire and (ii) the German translation of Yalom’s Questionnaire on Experiencing in Group Psychotherapy. Results The majority of patients rate their psychotherapy as highly profitable despite the mask. In individual therapy, face masks seem to have a rather low impact on subjective experience of psychotherapy and the relationship to the psychotherapist. Most patients reported using alternative facial expressions and expressions. In the interactional group therapy, masks were rather hindering. On the healthcare professional side, there were more frequent negative associations of face masks in relation to (i) experiencing connectedness with colleagues, (ii) forming relationships, and (iii) therapeutic treatment. Discussion Information should be given to patients about the possible effects of face masks on the recognition of emotions, possible misinterpretations and compensation possibilities through alternative stimuli (e.g., eye area) and they should be encouraged to ask for further information. Especially in group therapy, with patients from other cultural backgrounds and in cases of need for help (e.g., hearing impairment) or complex disorders, appropriate non-verbal gestures and body language should be used to match the intended emotional expression.